A non-aqueous electrolyte and secondary battery

By using carboxylic acid ester and compound of Structural Formula 1 in the lithium-ion battery, a stable passivation film is formed, which solves the problems of high-pressure electrode side reaction and electrolyte decomposition, and improves the fast charging and circulation of the battery performance and maintain good performance at high temperatures.

CN114552004BActive Publication Date: 2024-12-13SHENZHEN CAPCHEM TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210073247.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-21
Publication Date
2024-12-13
Estimated Expiration
2042-01-21

AI Technical Summary

Technical Problem

When existing lithium-ion batteries improve energy density and fast charging performance, it is difficult to take into account both the circulation performance and battery stability, especially the side reactions caused by high-pressure electrodes and electrolyte decomposition problems, resulting in poor fast charging performance of the battery.

Method used

A non-aqueous electrolyte solution containing a carboxylic acid ester with a high dielectric constant and a low viscosity and a compound represented by structural formula 1 as additives. By controlling the content ratio of electrolyte salts, carboxylic acid esters and additives, a stable and dense blunt blunt is formed. The film is decomposed to inhibit the side reaction of carboxylic acid ester and improves the ion conduction performance and the cycling performance of the battery.

Benefits of technology

It effectively improves the fast charging and circulation performance of lithium-ion batteries, reduces the internal resistance of the battery, extends the cycle life of the battery, and maintains good conductivity under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114552004B_ABST
    Figure CN114552004B_ABST
Patent Text Reader

Abstract

In order to overcome the problem that existing secondary batteries are difficult to balance energy density, cycle performance and fast charging performance, the present invention provides a non-aqueous electrolyte, including an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent includes a carboxylate, and the additive includes a compound shown in structural formula 1: wherein n is 0 or 1, A is selected from C or O, X is selected from or R1, R2 are independently selected from H, or R1 and R2 are not selected from H at the same time, and X, R1 and R2 contain at least one sulfur atom; the non-aqueous electrolyte satisfies the following conditions: 0.02≤an / m≤9, and 0.01%≤a≤5%, 5%≤m≤70%, 8%≤n≤25%. At the same time, the present invention also discloses a secondary battery including the above-mentioned non-aqueous electrolyte. The non-aqueous electrolyte provided by the present invention effectively reduces the internal resistance of the battery and improves the fast charging performance and cycle performance of the battery by limiting the content relationship of the compound shown in structural formula 1, the carboxylate and the electrolyte salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage battery devices, and in particular relates to a non-aqueous electrolyte and a secondary battery. Background Art

[0002] Lithium-ion batteries have been widely used in 3C digital products such as mobile phones and laptops, as well as new energy vehicles, due to their high operating voltage, wide operating temperature range, high energy density and power density, no memory effect, and long cycle life. In recent years, with the continuous development of thinner and lighter 3C digital products, the battery industry has higher and higher requirements for high energy density of lithium-ion batteries. At the same time, for user considerations, fast charging has become a basic requirement for batteries. Therefore, it is urgent to increase the energy density of lithium-ion batteries and improve fast charging performance.

[0003] At present, there are two main methods to improve the energy density of batteries. One is to increase the positive electrode charging cut-off voltage, and the other is to pressurize the active material layer of the electrode to achieve high density. However, after increasing the positive electrode charging cut-off voltage, the activity of the positive electrode will be further improved, and the side reactions between the positive electrode and the electrolyte will also intensify, which will lead to the dissolution of the positive electrode transition metal ions, thereby causing the battery cycle performance to deteriorate. In addition, the use of high-density electrodes can increase the load of the pole piece, thereby improving the overall energy density of the battery, but due to the low porosity of the high-density electrode, the battery's liquid retention will also be reduced, making it difficult for the electrolyte to penetrate the interface of the low-porosity pole piece, thereby increasing the contact internal resistance between the electrolyte and the electrode. During the long-term cycle process, the charge and discharge polarization becomes larger, which will cause a sudden dive due to lithium precipitation, and the high-density pole piece lithium ion conduction channel is tortuous, causing lithium ion transmission difficulties, so that the battery's fast charging performance is very poor. In summary, the existing technology for improving energy density will lead to the deterioration of the battery's cycle performance and fast charging performance. Therefore, how to make high-voltage, high-pressure lithium-ion batteries have good fast charging performance is an industry challenge that requires improvements at various levels such as electrode materials and electrolytes.

[0004] From the perspective of electrolyte, the existing technology often selects a carboxylate system with a high dielectric constant and low viscosity as a solvent to improve the fast charging performance of the battery. However, carboxylate is unstable under high voltage and is prone to produce decomposition products on the positive electrode side. The decomposition products migrate to the negative electrode and are reduced and accumulated on the surface of the negative electrode, causing the battery impedance to increase. It is easy to deteriorate rapidly in the later stage of the cycle. Therefore, there is an urgent need to improve from the perspective of electrolyte. Summary of the invention

[0005] In view of the problem that existing secondary batteries are difficult to balance energy density, cycle performance and fast charging performance, the present invention provides a non-aqueous electrolyte and a secondary battery.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In one aspect, the present invention provides a non-aqueous electrolyte, comprising an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent comprises a carboxylate, and the additive comprises a compound represented by structural formula 1:

[0008]

[0009] Wherein n is 0 or 1, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2;

[0010] The non-aqueous electrolyte meets the following conditions:

[0011] 0.02≤an / m≤9,

[0012] and 0.01%≤a≤5%, 5%≤m≤70%, 8%≤n≤25%;

[0013] Wherein, a is the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte, in %;

[0014] m is the mass percentage of carboxylic acid ester in the non-aqueous electrolyte, in %;

[0015] n is the mass percentage of electrolyte salt in the non-aqueous electrolyte, in %;

[0016] The conductivity of the non-aqueous electrolyte at 25° C. is greater than or equal to 5 mS / cm.

[0017] Optionally, the non-aqueous electrolyte satisfies the following conditions:

[0018] 0.2≤an / m≤4.

[0019] Optionally, the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte is 0.05% to 3%.

[0020] Optionally, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte is 10% to 60%.

[0021] Optionally, the mass percentage n of the electrolyte salt in the non-aqueous electrolyte is 10% to 20%.

[0022] Preferably, the electrolyte salt is selected from one or more of LiPF6, LiPO2F2, LiBF4, LiClO4, LiCF3SO3, LiN(SO2CF3)2 and LiN(SO2F)2.

[0023] Optionally, the compound represented by structural formula 1 is selected from one or more of the following compounds 1 to 22:

[0024]

[0025]

[0026]

[0027] Optionally, the carboxylic acid ester includes one or more of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, 2,2-difluoroethyl acetate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate and ethyl trimethyl acetate.

[0028] Optionally, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, an unsaturated phosphate compound, a nitrile compound and a lithium oxalate borate salt;

[0029] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.01% to 30%.

[0030] Preferably, the cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate;

[0031] The sultone compound is selected from at least one of 1,3-propane sultone, 1,4-butane sultone or 1,3-propylene sultone;

[0032] The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene carbonate, fluoroethylene carbonate or the compound shown in structural formula 2.

[0033]

[0034] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;

[0035] The unsaturated phosphate compound is selected from at least one of the compounds shown in Structural Formula 3:

[0036]

[0037] In the structural formula 3, R31 , R 32 , R 32 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group;

[0038] The nitrile compound is selected from one or more of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile;

[0039] The lithium oxalatoborate salt is selected from one or more of Li[B(C2O4)2] and Li[B(C2O4)F2].

[0040] Preferably, the non-aqueous organic solvent further comprises one or more of cyclic carbonates, linear carbonates and ethers.

[0041] Preferably, the cyclic carbonate includes one or more of vinylene carbonate, propylene carbonate and ethylene carbonate; the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; the ether includes one or more of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0042] On the other hand, the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above, wherein the positive electrode comprises a positive electrode material layer, and the compaction density of the positive electrode material layer is 3.5 g / cm 3 The negative electrode comprises a negative electrode material layer, and the compaction density of the negative electrode material layer is 1.5 g / cm 3 As a result, a high energy density battery can be obtained.

[0043] According to the non-aqueous electrolyte provided by the present invention, in view of the characteristics of high compaction density and high voltage in the high energy density battery system, a carboxylic acid ester with high dielectric constant and low viscosity is selected as the solvent of the non-aqueous electrolyte to improve the wetting ability and ion conductivity of the non-aqueous electrolyte for the positive and negative electrodes, and improve the fast charging capability of the battery. In response to the problem that carboxylates are unstable and easily decomposed under high voltage, the inventors have found through extensive research that adding the compound shown in structural formula 1 as an additive to the non-aqueous electrolyte can effectively inhibit the side reactions of the carboxylates in the battery, and the content of the electrolyte salt and the carboxylates jointly affect the ion conductivity of the non-aqueous electrolyte. By controlling the parameter range of the mass percentage a of the compound shown in structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylates in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte, and making them satisfy the relationship 0.02≤an / m≤9, a stable and dense passivation film can be formed on the positive and negative electrodes to effectively prevent the oxidation of the carboxylates. At the same time, the content relationship of the compound shown in structural formula 1, the carboxylates and the electrolyte salt is limited, which effectively reduces the internal resistance of the battery and improves the fast charging performance and cycle performance of the battery. DETAILED DESCRIPTION

[0044] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] An embodiment of the present invention provides a non-aqueous electrolyte, including an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent includes a carboxylate, and the additive includes a compound shown in Structural Formula 1:

[0046]

[0047] Wherein n is 0 or 1, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2;

[0048] The non-aqueous electrolyte meets the following conditions:

[0049] 0.02≤an / m≤9,

[0050] and 0.01%≤a≤5%, 5%≤m≤70%, 8%≤n≤25%;

[0051] Wherein, a is the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte, in %;

[0052] m is the mass percentage of carboxylic acid ester in the non-aqueous electrolyte, in %;

[0053] n is the mass percentage of electrolyte salt in the non-aqueous electrolyte, in %;

[0054] The conductivity of the non-aqueous electrolyte at 25° C. is greater than or equal to 5 mS / cm.

[0055] Carboxylates are unstable under high voltages and are prone to produce decomposition products on the positive electrode side. Some of the decomposition products migrate to the negative electrode and are reduced, and accumulate on the negative electrode surface, causing the battery impedance to continue to increase, which is not conducive to improving the battery cycle performance. The inventors have found through extensive research that adding the compound shown in Structural Formula 1 as an additive to a non-aqueous electrolyte can effectively inhibit the side reactions of carboxylates in the battery. It is speculated that this is because the compound shown in Structural Formula 1 participates in film formation on both the positive and negative electrodes, and the passivation film formed can effectively inhibit the decomposition reaction of carboxylates on the positive electrode surface, reduce the generation of oxidation by-products, and inhibit the reduction and accumulation of oxidation by-products on the negative electrode surface. Therefore, the continuous increase in the impedance of the passivation film on the positive and negative electrode surfaces can be avoided during the cycle process, while also ensuring the carboxylates' effect on improving the battery's fast charging performance; and the content of the electrolyte salt is related to the carboxylates. The content of ester jointly affects the viscosity and ion conductivity of the non-aqueous electrolyte. By controlling the parameter range of the mass percentage a of the compound shown in Structural Formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylate in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte, and making them satisfy the relationship 0.02≤an / m≤9, a stable and dense passivation film can be formed on the positive and negative electrodes to effectively prevent the oxidation of the carboxylate. At the same time, limited by the content relationship of the compound shown in Structural Formula 1, the carboxylate and the electrolyte salt, the internal resistance of the battery is effectively reduced, and the fast charging performance and cycle performance of the battery are improved.

[0056] The conductivity of the non-aqueous electrolyte at 25° C. is greater than or equal to 5 mS / cm, which can make the film-forming effect of the compound represented by structural formula 1 better and ensure that the electrolyte has good high-temperature performance.

[0057] In some preferred embodiments, the conductivity of the non-aqueous electrolyte at 25°C is 6.0mS / cm to 9.0mS / cm, which can further ensure that the negative electrode does not precipitate lithium and improve the high-temperature cycle performance of the battery. The higher the conductivity of the electrolyte at room temperature 25°C, the better the performance of the battery. However, if the content of a certain type of organic solvent is increased simply to improve the room-temperature conductivity, the side reaction will increase due to the excessive addition ratio of a certain type of organic solvent, which will affect the battery's cycle life and other performance to a certain extent.

[0058] In some embodiments, when n is 0, the compound represented by structural formula 1 is:

[0059]

[0060] Wherein, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2.

[0061] In some embodiments, when n is 1, the compound represented by structural formula 1 is:

[0062]

[0063] Wherein, A is selected from C or O, and X is selected from R1 and R2 are each independently selected from H, R1 and R2 are not simultaneously selected from H, and at least one sulfur atom is contained in X, R1 and R2.

[0064] In a preferred embodiment, the non-aqueous electrolyte satisfies the following conditions:

[0065] 0.2≤an / m≤4.

[0066] By correlating the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylate in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte, it is possible to comprehensively consider the combined effects of the compound represented by structural formula 1, the carboxylate and the electrolyte salt on the fast charging performance of the battery, thereby obtaining a non-aqueous electrolyte suitable for high-pressure batteries and improving the cycle performance of the battery under high-rate charge and discharge conditions.

[0067] In a specific embodiment, the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte can be 0.01%, 0.05%, 0.1%, 0.12%, 0.15%, 0.3%, 0.5%, 0.8%, 0.9%, 1.0%, 1.2%, 1.4%, 1.7%, 1.9%, 2.1%, 2.2%, 2.4%, 2.7%, 2.9%, 3.1%, 3.3%, 3.5%, 3.7%, 4.2%, 4.4%, 4.7%, 4.9% or 5.0%.

[0068] In a preferred embodiment, the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte is 0.05% to 3%.

[0069] If the content of the compound shown in Structural Formula 1 in the non-aqueous electrolyte is too little, it will affect the quality of the passivation film formed on the surface of the positive and negative electrodes, and it will be difficult to effectively inhibit the side reaction of the carboxylic acid ester; if the content of the compound shown in Structural Formula 1 in the non-aqueous electrolyte is too much, it will cause the viscosity of the non-aqueous electrolyte to increase, affecting the wetting of the non-aqueous electrolyte on the positive and negative electrode materials, resulting in an increase in impedance and affecting the battery performance.

[0070] In a specific embodiment, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte can be 5%, 8%, 10%, 13%, 16%, 17%, 19%, 21%, 22%, 24%, 27%, 29%, 31%, 33%, 35%, 37%, 42%, 44%, 47%, 49%, 50%, 53%, 55%, 58%, 60%, 61%, 63%, 65%, 68% or 70%.

[0071] In a preferred embodiment, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte is 10% to 60%.

[0072] By adding carboxylic acid ester as a non-aqueous organic solvent to the non-aqueous electrolyte, the fast charging performance of the battery can be improved. However, if the amount of carboxylic acid ester added is too little, the conductivity of the non-aqueous electrolyte will be low, affecting the cycle performance of the battery; adding too much carboxylic acid ester will reduce the stability of the non-aqueous electrolyte, which is also not conducive to improving the cycle performance of the battery.

[0073] In a specific embodiment, the mass percentage n of the electrolyte salt in the non-aqueous electrolyte can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%.

[0074] In a preferred embodiment, the mass percentage n of the electrolyte salt in the non-aqueous electrolyte is 10% to 20%.

[0075] The alkali metal ions formed by the dissociation of the electrolyte salt in the non-aqueous electrolyte are embedded and deintercalated between the positive and negative electrodes to complete the charge and discharge cycle. The concentration of the electrolyte salt directly affects the transfer speed of the alkali metal ions, and the transfer speed of the alkali metal ions affects the potential change of the negative electrode. During the rapid charging process of the battery, it is necessary to increase the movement speed of the alkali metal ions as much as possible to prevent the negative electrode potential from dropping too fast, resulting in the formation of lithium dendrites, which poses a safety hazard to the battery, and at the same time prevent the battery's cycle capacity from decaying too quickly. When the content of the electrolyte salt is too low, the embedding and extraction efficiency of the alkali metal ions between the positive and negative electrodes will be reduced, and the demand for fast charging of the battery cannot be met; when the content of the electrolyte salt is too high, the viscosity of the non-aqueous electrolyte will increase, which is also not conducive to the improvement of the embedding and extraction efficiency of the alkali metal ions, and increases the internal resistance of the battery.

[0076] In some embodiments, the electrolyte salt includes one or more of lithium salt, sodium salt, potassium salt, magnesium salt, zinc salt and aluminum salt. In a preferred embodiment, the electrolyte salt is selected from lithium salt or sodium salt.

[0077] In a preferred embodiment, the electrolyte salt is selected from LiPF6, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiN(SO2F)2, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium carboxylate with less than 4 carbon atoms, lithium tetraphenylborate and lithium imide. Specifically, the electrolyte salt can be inorganic electrolyte salts such as LiBF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, LiWF7; fluorophosphate electrolyte salts such as LiPF6; tungstic acid electrolyte salts such as LiWOF5; carboxylic acid electrolyte salts such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, CF3CF2CF2CF2CO2Li; sulfonic acid electrolyte salts such as CH3SO3Li; LiN(FCO2)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO 2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethanedisulfonyl lithium imide, cyclic 1,3-perfluoropropanedisulfonyl lithium imide, LiN(CF3SO2)(C4F9SO2) and other imide electrolyte salts; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3 and other methyl electrolyte salts; and LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2 and other fluorine-containing organic electrolyte salts, etc.

[0078] In a preferred embodiment, the electrolyte salt is selected from one or more of LiPF6, LiPO2F2, LiBF4, LiClO4, LiCF3SO3, LiN(SO2CF3)2 and LiN(SO2F)2.

[0079] If the electrolyte salt is selected from other salts such as sodium salt, potassium salt, magnesium salt, zinc salt or aluminum salt, the lithium in the above lithium salt can be replaced with sodium, potassium, magnesium, zinc or aluminum.

[0080] In a preferred embodiment, the sodium salt is selected from at least one of sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium trifluoromethanesulfonate (NaFSI), and sodium bistrifluoromethanesulfonate (NaTFSI).

[0081] The above analysis is only based on the influence of each parameter or multiple parameters on the battery when they exist alone. However, in the actual battery application process, there is a certain intrinsic correlation between parameters such as the mass percentage a of the compound shown in structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte. Through a large number of experiments, the inventors have summarized the relationship 0.02≤an / m≤9, which can effectively serve as a basis for screening secondary batteries with high energy density, fast charging performance and excellent cycle performance.

[0082] In some embodiments, the compound represented by structural formula 1 is selected from one or more of the following compounds 1 to 22:

[0083]

[0084]

[0085]

[0086] It should be noted that the above are only preferred compounds of the present invention and do not represent limitations on the present invention.

[0087] A person skilled in the art, knowing the structural formula of the compound shown in Structural Formula 1, can know the preparation method of the above compound according to the common knowledge in the field of chemical synthesis. For example, Compound 7 can be prepared by the following method:

[0088] Sorbitol, dimethyl carbonate, methanol, alkaline substance catalyst potassium hydroxide and organic solvent such as DMF are placed in a reaction container, and reacted under heating conditions for several hours. Then, a certain amount of oxalic acid is added to adjust the pH to neutral. After filtering and recrystallization, intermediate product 1 can be obtained. Then, intermediate product 1, carbonate, dichlorothionyl, etc. are subjected to esterification reaction under high temperature conditions to obtain intermediate product 2. Then, intermediate product 2 is oxidized with an oxidant such as sodium periodate to obtain compound 7.

[0089] In some embodiments, the carboxylic acid ester includes one or more of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, 2,2-difluoroethyl acetate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate, and ethyl trimethyl acetate.

[0090] In some embodiments, the non-aqueous organic solvent further comprises one or more of an ether solvent, a nitrile solvent, and a carbonate solvent.

[0091] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, one or more of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but is not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. There is no special restriction on the amount of ether compounds added, and it is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. In the case where the volume ratio of the non-aqueous organic solvent is 100%, the volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less. When two or more ether compounds are used in combination, the total amount of the ether compounds can be made to meet the above range. When the amount of ether compounds added is within the above preferred range, it is easy to ensure the improvement effect of ion conductivity brought about by the increase in lithium ion dissociation degree and the decrease in viscosity of the chain ether. In addition, when the negative electrode active material is a carbon material, the phenomenon of co-embedding of chain ethers and lithium ions can be suppressed, so that the input-output characteristics and charge-discharge rate characteristics can reach an appropriate range.

[0092] In some embodiments, the nitrile solvent may specifically be, but is not limited to, one or more of acetonitrile, glutaronitrile, and malononitrile.

[0093] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate can be specifically but not limited to one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonate can be specifically but not limited to one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). There is no special restriction on the content of the cyclic carbonate, and it is arbitrary within the range that does not significantly damage the effect of the secondary battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of the non-aqueous organic solvent of the non-aqueous electrolyte. By setting this range, the conductivity can be reduced due to the reduction of the dielectric constant of the non-aqueous electrolyte, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually less than 90% by volume, preferably less than 85% by volume, and more preferably less than 80% by volume. By setting this range, the oxidation / reduction tolerance of the nonaqueous electrolyte can be improved, thereby helping to improve the stability during high temperature storage. The content of the linear carbonate is not particularly limited, and relative to the total amount of the nonaqueous organic solvent of the nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of the linear carbonate in the above-mentioned range, it is easy to make the viscosity of the nonaqueous electrolyte reach an appropriate range, suppress the reduction of ionic conductivity, and then help to make the output characteristics of the nonaqueous electrolyte battery reach a good range. When two or more linear carbonates are used in combination, the total amount of the linear carbonate is made to meet the above-mentioned range.

[0094] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.

[0095] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the secondary battery of the present invention. Relative to the total amount of non-aqueous organic solvent in the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can meet the above range. When the amount of sulfone solvent added is within the above range, an electrolyte with excellent high temperature storage stability tends to be obtained.

[0096] In some embodiments, the non-aqueous electrolyte further includes auxiliary additives, and the auxiliary additives include at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, unsaturated phosphate compounds, nitrile compounds and lithium oxalate borate salt.

[0097] In a preferred embodiment, the cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate;

[0098] The sultone compound is selected from at least one of 1,3-propane sultone, 1,4-butane sultone or 1,3-propylene sultone;

[0099] The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene carbonate, fluoroethylene carbonate or the compound shown in structural formula 2.

[0100]

[0101] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;

[0102] The unsaturated phosphate compound is selected from at least one of the compounds shown in Structural Formula 3:

[0103]

[0104] In the structural formula 3, R 31 , R 32 , R32 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group.

[0105] In a preferred embodiment, the unsaturated phosphate compound may be at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0106] The nitrile compound is selected from one or more of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile;

[0107] The lithium oxalatoborate salt is selected from one or more of Li[B(C2O4)2] and Li[B(C2O4)F2].

[0108] In other embodiments, the auxiliary additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.

[0109] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.01% to 30%.

[0110] It should be noted that, unless otherwise specified, in general, the amount of any one of the optional substances in the auxiliary additives added to the non-aqueous electrolyte is less than 10%, preferably, the amount added is 0.1-5%, and more preferably, the amount added is 0.1% to 2%. Specifically, the amount of any one of the optional substances in the auxiliary additives can be 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.

[0111] In some embodiments, when the auxiliary additive is selected from fluoroethylene carbonate, the amount of the fluoroethylene carbonate added is 0.05% to 30% based on the total mass of the non-aqueous electrolyte as 100%.

[0112] Another embodiment of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above, wherein the positive electrode comprises a positive electrode material layer, and the compaction density of the positive electrode material layer is 3.5 g / cm 3 The negative electrode comprises a negative electrode material layer, and the compaction density of the negative electrode material layer is 1.5 g / cm 3 above.

[0113] In a preferred embodiment, the compaction density of the positive electrode material layer is 3.8-4.15 g / cm 3 .

[0114] In a preferred embodiment, the compaction density of the negative electrode material layer is 1.65-1.85 g / cm 3 .

[0115] In some embodiments, the porosity of the positive electrode material and the negative electrode material is 50% or less.

[0116] In a preferred embodiment, the porosity of the positive electrode material and the negative electrode material is 10%-35%.

[0117] In some embodiments, the maximum charging cut-off voltage of the secondary battery is ≥4.4V.

[0118] In some embodiments, the positive electrode material layer includes a positive electrode active material. The type and content of the positive electrode active material are not particularly limited and can be selected according to actual needs, as long as it is a positive electrode active material or a conversion-type positive electrode material that can reversibly embed / de-embed metal ions (lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, aluminum ions, etc.).

[0119] In a preferred embodiment, the battery is a lithium-ion battery, and its positive electrode active material can be selected from LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1, and the positive electrode active material can also be selected from one or more of sulfide, selenide and halide. More preferably, the positive electrode active material can be selected from LiCoO2, LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0120] In a preferred embodiment, the secondary battery is a sodium ion battery, and its positive electrode active material can be selected from one or more of metallic sodium, carbon material, alloy material, overplated metal oxide, overplated metal sulfide, phosphorus-based material, titanate material, and Prussian blue material. The carbon material can be selected from one or more of graphite, soft carbon, and hard carbon. The alloy material can be selected from an alloy material composed of at least two of Si, Ge, Sn, Pb, and Sb. The alloy material can also be selected from an alloy material composed of at least one of Si, Ge, Sn, Pb, and Sb and C. The chemical formula of the overplated metal oxide and the overplated metal sulfide is M1 x N y, M1 can be selected from one or more of Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V, N is selected from O or S, the phosphorus-based material can be selected from one or more of red phosphorus, white phosphorus, and black phosphorus, and the titanate material can be selected from Na2Ti3O7, Na2Ti6O 13 、Na4Ti5O 12 、Li4Ti5O 12 , NaTi2(PO4)3, wherein the molecular formula of the Prussian blue material is Na x M[M′(CN)6] y ·zH2O, where M is a transition metal, M′ is a transition metal, 0 <x≤2,0.8≤y<1,0<z≤20。

[0121] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer covers a surface of the positive electrode current collector.

[0122] The positive electrode current collector is selected from a metal material that can conduct electrons. Preferably, the positive electrode current collector includes one or more of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.

[0123] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.

[0124] The positive electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.

[0125] The positive electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0126] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based negative electrode, a tin-based negative electrode, a silicon-based negative electrode, a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode, and an aluminum negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include one or more of silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.

[0127] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail here.

[0128] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are mixed to obtain the negative electrode material layer. The negative electrode binder and the negative electrode conductive agent may be the same as the positive electrode binder and the positive electrode conductive agent, respectively, and will not be described in detail here.

[0129] In some embodiments, the battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.

[0130] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.

[0131] The present invention is further described below by way of examples.

[0132] The compounds involved in the following examples and comparative examples are shown in the following table:

[0133]

[0134] Table 1 Parameter design of embodiments and comparative examples

[0135]

[0136]

[0137] Example 1

[0138] This embodiment is used to illustrate the battery and the preparation method thereof disclosed in the present invention, and includes the following steps:

[0139] 1) Preparation of electrolyte: solvent ethylene carbonate (EC), diethyl carbonate (DEC) and carboxylic acid ester are mixed, and then lithium hexafluorophosphate (LiPF6) and additives are added. The contents of carboxylic acid ester, lithium hexafluorophosphate and additives in the electrolyte are shown in Table 1, and the contents are calculated as a percentage of the total mass of the electrolyte.

[0140] 2) Preparation of positive electrode

[0141] The positive electrode active material LiCoO2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with an ultrasonic welder to obtain a positive electrode plate. The thickness of the positive electrode plate is 80 to 150 μm, and the compaction density of the positive electrode plate is 4.13 g / cm 3 .

[0142] 3) Preparation of negative electrode plate

[0143] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled, and welded with a nickel lead wire using an ultrasonic welder to obtain a negative electrode plate. The compacted density of the negative electrode plate was 1.81 g / cm 3 .

[0144] 4) Preparation of battery cells

[0145] A polyethylene microporous membrane with a thickness of 20 μm is placed between the positive plate and the negative plate as a separator, and then the sandwich structure consisting of the positive plate, the negative plate and the separator is wound, and then the wound body is flattened and placed in an aluminum-plastic film. After the lead wires of the positive and negative electrodes are led out respectively, the aluminum-plastic film is hot-pressed and sealed to obtain a battery cell to be injected with liquid.

[0146] 5) Battery filling and formation

[0147] In a glove box with a dew point controlled below -40°C, the prepared electrolyte is injected into the battery cell through the injection hole, and the amount of electrolyte must be sufficient to fill the gaps in the battery cell. Then the formation is carried out according to the following steps: 0.05C constant current charging for 180 minutes, 0.1C constant current charging for 180 minutes, leaving it for 24 hours, shaping and sealing it, and then further charging it at a constant current of 0.2C to a cut-off voltage of 4.50V, leaving it at room temperature for 24 hours, and discharging it at a constant current of 0.2C to 3.0V.

[0148] Embodiments 2 to 43

[0149] Examples 2 to 43 are used to illustrate the battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that:

[0150] The electrolyte additive components shown in Table 1 were used.

[0151] Comparative Examples 1 to 13

[0152] Comparative Examples 1 to 13 are used to compare and illustrate the battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that:

[0153] The electrolyte additive components shown in Table 1 were used.

[0154] Performance Testing

[0155] The lithium-ion battery prepared above was subjected to the following performance tests:

[0156] At 25°C, the conductivity of the non-aqueous electrolyte was tested, and the conductivity of Examples 1 to 43, Comparative Examples 1 to 5, Comparative Examples 7 to 11 and Comparative Example 13 were all above 5 mS / cm, while the conductivity of Comparative Example 6 and Comparative Example 12 was lower than 5 mS / cm.

[0157] At 45°C, charge at a constant current of 3C to 4.50V, then charge at a constant voltage of 4.50V until the current drops to 0.05C, then discharge at a constant current of 3C to 3.0V. Repeat this cycle for 400 weeks. Record the discharge capacity and discharge DCIR of the first week, as well as the discharge capacity and discharge DCIR of the 400th week. Calculate the capacity retention rate and DCIR growth rate as follows:

[0158] Capacity retention rate (%) = (discharge capacity at the 400th week ÷ discharge capacity at the 1st week) × 100%;

[0159] DCIR growth rate (%) = (400th week discharge DCIR - 1st week discharge DCIR) / 1st week discharge DCIR.

[0160] (1) The test results obtained in Examples 1 to 30 and Comparative Examples 1 to 13 are entered in Table 2.

[0161] Table 2

[0162]

[0163]

[0164] From the test results of Examples 1-30 and Comparative Examples 1 to 13, it can be seen that the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylate in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte have an obvious correlation. When the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylate in the non-aqueous electrolyte, and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte satisfy the relationship 0.02≤an / m≤9, and 0.01%≤a≤5%, 5%≤m≤70%, 8%≤n≤25%, the obtained lithium ion battery has a higher cycle capacity retention rate and a lower impedance increase under high current fast charging conditions. The growth rate is speculated to be due to the fact that the compound shown in structural formula 1 participates in the film formation on both the positive and negative electrodes, and the formed passivation film can effectively inhibit the decomposition reaction of the carboxylate on the positive electrode surface, reduce the generation of oxidation by-products, and inhibit the reduction and accumulation of oxidation by-products on the negative electrode surface. Therefore, the continuous increase of the impedance of the passivation film on the positive and negative electrode surfaces can be avoided during the cycle, and the carboxylate can also ensure the improvement of the fast charging performance of the battery, thereby inhibiting the capacity attenuation; the content of the electrolyte salt and the content of the carboxylate jointly affect the viscosity and ion conductivity of the non-aqueous electrolyte; under the control of comprehensive conditions, it is conducive to the formation of a dense passivation film on the positive and negative electrode surfaces, which effectively reduces the internal resistance of the battery and improves the fast charging performance and cycle performance of the battery.

[0165] From the test results of Comparative Examples 1 to 5, it can be seen that even if the a value, n value and m value all meet the parameter range limits, if the an / m value is too large or too small, the fast charging performance of the battery will be deteriorated, indicating that the mass percentage a of the compound represented by structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte have a mutual influence on each other. When and only when the three reach a good balance, the fast charging performance of the battery can be significantly improved. At the same time, it can be seen from the test results of Comparative Examples 6 to 13 that when one of the parameters a, n and m exceeds the specified range, even if the relationship 0.02≤an / m≤9 is satisfied, the capacity retention rate and impedance growth rate of the battery under high current fast charging conditions are also poor, indicating that when the mass percentage a of the compound shown in structural formula 1 in the non-aqueous electrolyte, the mass percentage m of the carboxylic acid ester in the non-aqueous electrolyte and the mass percentage n of the electrolyte salt in the non-aqueous electrolyte are too high or too low, the formation of the passivation film on the surface of the positive and negative electrodes and the stability of the non-aqueous electrolyte under fast charging conditions will be affected.

[0166] It can be seen from the test results of Examples 1 to 30 that when the relationship satisfies 0.2≤an / m≤4, the lithium-ion battery has the best comprehensive battery performance.

[0167] It can be seen from the test results of Examples 8 to 12 that in the lithium ion battery provided by the present invention, as the content of carboxylate in the solvent increases, the capacity retention rate and impedance growth rate of the battery under fast charging conditions first increase and then decrease, indicating that adding a proper amount of carboxylate is beneficial to improving the conductivity of the non-aqueous electrolyte, which is a prerequisite for improving the fast charging performance of lithium ion batteries. However, carboxylate is unstable. When the content of carboxylate is too high or there is not enough compound shown in structural formula 1 to inhibit the decomposition of carboxylate, carboxylate is prone to side reactions, thereby decomposing to increase the thickness of the passivation film on the positive and negative electrode surfaces, and reduce the conductivity of the non-aqueous electrolyte, affecting the capacity of the lithium ion battery and increasing the impedance.

[0168] It can be seen from the test results of Examples 19 to 26 that as the content of the compound represented by Structural Formula 1 increases, the content of the carboxylate in the solvent needs to be increased at the same time to effectively improve the fast charging cycle performance of the battery. When the content of the compound represented by Structural Formula 1 is high and the content of the carboxylate is insufficient, as shown in Example 25, the capacity retention rate and impedance growth rate of the lithium-ion battery are slightly worse than those of Example 26, indicating that the passivation film formed by the compound represented by Structural Formula 1 is relatively dense, and sufficient carboxylate is required to reduce the viscosity of the non-aqueous electrolyte, thereby ensuring the wetting of the electrode material by the non-aqueous electrolyte and improving the ion conductivity.

[0169] (2) The test results obtained in Example 10 and Examples 31 to 35 are entered in Table 3.

[0170] Table 3

[0171]

[0172] It can be seen from the test results of Example 10 and Examples 31 to 35 that when different compounds represented by structural formula 1 are used as additives to non-aqueous electrolytes, the relationship of 0.02≤an / m≤9 is also satisfied, indicating that the cyclic sulfur-containing groups commonly contained in the compounds represented by different structural formulas 1 play a decisive role in the formation of the passivation film on the surface of the positive and negative electrodes, and the passivation film rich in S elements produced by its decomposition has a good isolation effect on the carboxylic acid ester, thereby avoiding the continuous decomposition of the carboxylic acid ester on the surface of the positive and negative electrode materials. The relationship provided by the present invention is universal for the compounds represented by different structural formulas 1, and has an improving effect on the fast charging cycle performance of lithium-ion batteries.

[0173] (3) The test results obtained in Example 10 and Examples 36 to 38 are entered in Table 4.

[0174] Table 4

[0175]

[0176] It can be seen from the test results of Example 10 and Examples 36 to 38 that when different carboxylates are used as non-aqueous organic solvents, the relationship of 0.02≤an / m≤9 is also satisfied, indicating that different carboxylates have the effect of reducing the viscosity of the non-aqueous electrolyte and improving the conductivity, and also have a good coordination effect with the compound shown in Structural Formula 1, and can synergistically improve the capacity retention rate of the battery under fast charging conditions and reduce the impedance growth rate.

[0177] (4) The test results obtained in Example 10 and Examples 39 to 43 are entered in Table 5.

[0178] Table 5

[0179]

[0180] It can be seen from the test results of Example 10 and Examples 39 to 43 that, on the basis of the battery provided by the present invention, adding PS (1,3-propane sultone), DTD (vinyl sulfate), tripropargyl phosphate, succinonitrile or LiODFB as an auxiliary additive can further improve the capacity retention performance of the battery and reduce the impedance growth of the battery. It is speculated that this is because there is a certain common decomposition reaction between the compound shown in Structural Formula 1 and the added PS (1,3-propane sultone), DTD (vinyl sulfate), tripropargyl phosphate, succinonitrile or LiODFB, which can jointly participate in the formation of a passivation film on the electrode surface, and the obtained passivation film can improve the stability of the non-aqueous electrolyte, maintain the stability of the battery cycle and the performance of withstanding large currents.

[0181] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, It is characterized in that The method comprises an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent comprises a carboxylate, and the additive comprises one or more of the following compounds 1 to 3, 5 to 22: The non-aqueous electrolyte meets the following conditions: 0.02≤an / m≤9, And 0.01%≤a≤5%, 10%≤m≤60%, 8%≤n≤25%; Wherein, a is the mass percentage of compounds 1-3, 5-22 in the non-aqueous electrolyte, unit is %; m is the mass percentage of carboxylic acid ester in the non-aqueous electrolyte, unit is %; n is the mass percentage of electrolyte salt in the non-aqueous electrolyte, unit is %; The conductivity of the non-aqueous electrolyte at 25° C. is 6.0 mS / cm to 9.0 mS / cm.

2. The nonaqueous electrolyte according to claim 1, It is characterized in that The non-aqueous electrolyte meets the following conditions: 0.2≤an / m≤4.

3. The nonaqueous electrolyte according to claim 1, It is characterized in that The mass percentage a of compounds 1-3 and 5-22 in the non-aqueous electrolyte is 0.05%-3%.

4. The nonaqueous electrolyte according to claim 1, It is characterized in that The mass percentage n of the electrolyte salt in the non-aqueous electrolyte is 10% to 20%.

5. The nonaqueous electrolyte according to claim 1, It is characterized in that The electrolyte salt is selected from LiPF 6 、LiPO 2 F 2 , LiBF 4 、LiClO 4 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 and LiN(SO 2 F) 2 One or more of .

6. The nonaqueous electrolyte according to claim 1, It is characterized in that The carboxylic acid ester includes one or more of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, 2,2-difluoroethyl acetate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate and ethyl trimethyl acetate.

7. The nonaqueous electrolyte according to claim 1, It is characterized in that The non-aqueous electrolyte also includes auxiliary additives, and the auxiliary additives include at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, unsaturated phosphate compounds, nitrile compounds and lithium oxalate borate salt.

8. The nonaqueous electrolyte according to claim 7, It is characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.01% to 30%.

9. The nonaqueous electrolyte according to claim 7, It is characterized in that The cyclic sulfate ester compound is selected from at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate; The sultone compound is selected from at least one of 1,3-propane sultone, 1,4-butane sultone or 1,3-propylene sultone; The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene carbonate, fluoroethylene carbonate or the compound shown in structural formula 2. Structural formula 2 In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group; The unsaturated phosphate compound is selected from at least one of the compounds shown in Structural Formula 3: Structural formula 3 In the structural formula 3, R 31 , R 32 , R 32 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 ) 3 , m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; The nitrile compound is selected from one or more of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile; The lithium oxalate borate salt is selected from Li[B(C 2 O 4 ) 2 ] and Li[B(C 2 O 4 )F 2 ] one or more.

10. The nonaqueous electrolyte according to claim 1, It is characterized in that The non-aqueous organic solvent further comprises one or more of cyclic carbonates, linear carbonates and ethers.

11. The nonaqueous electrolyte according to claim 10, It is characterized in that The cyclic carbonate includes one or more of vinylene carbonate, propylene carbonate and ethylene carbonate; the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; the ether includes one or more of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

12. A secondary battery, It is characterized in that The invention comprises a positive electrode, a negative electrode and a non-aqueous electrolyte according to any one of claims 1 to 11, wherein the positive electrode comprises a positive electrode material layer, and the compaction density of the positive electrode material layer is 3.5 g / cm 3 The negative electrode comprises a negative electrode material layer, and the compaction density of the negative electrode material layer is 1.5 g / cm 3 above.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and lithium ion battery

    CN109950620A

  • Additive for battery electrolyte, lithium ion battery electrolyte and lithium ion battery

    CN110931863A

  • Lithium ion battery electrolyte considering high and low temperature performance and lithium ion battery

    CN112290091A

  • High-compaction lithium ion battery

    CN113659206A

  • Non-aqueous electrolyte solution for batteries, lithium secondary battery precursor, lithium secondary battery, and method for producing lithium secondary battery

    CN115117446A